Exploring the Volatility, Phase Transitions, and Solubility Properties of Five Halogenated Benzaldehydes - Ana R. R. P. Almeida; Bruno D. A. Pinheiro; Gastón P. León; Bogdan Postolnyi; João P. Araújo; Manuel J. S. Monte (Molecules)
Halogenated benzaldehydes possess unique chemical properties that render them valuable in pharmaceutical synthesis, pesticide formulation, and dye production. However, thorough thermodynamic data for these compounds remain scarce. This study aims to fill this knowledge gap by investigating key physical properties of several halogenated benzaldehydes, namely 4-chlorobenzaldehyde, 4-bromobenzaldehyde, 2,3-dichlorobenzaldehyde, 2,4-dichlorobenzaldehyde, and 2,6-dichlorobenzaldehyde. The physical properties determined in this study include volatility, phase transitions, and water solubility, all of which are crucial for predicting the environmental fate of these compounds. The vapor pressures of both crystalline and liquid phases were measured using a reliable static method, allowing for the determination of standard molar enthalpies, entropies, and Gibbs energies of sublimation and vaporization, as well as their triple points. The melting temperature and molar enthalpy, along with the isobaric molar heat capacity of the crystalline phase, were assessed using differential scanning calorimetry. Water solubility was evaluated at 25 °C through the saturation shake-flask method, complemented by ultra-violet visible spectroscopy. By combining sublimation and solubility data, additional properties such as Gibbs energies of hydration and Henry’s law constants were derived. The experimental results were integrated into existing databases, enhancing the predictive models for properties including melting temperature, vapor pressure, solubility, Gibbs energy of hydration, and Henry’s constant. These findings significantly improve the environmental modeling capabilities, providing valuable insights into the mobility and fate of halogenated benzaldehydes in various environmental contexts.